Dynamic analysis of flexible space shuttle remote manipulator system with large payloads - Wiedemann, Simon M.; Kirk, Colin L. (Cranfield University; School of Engineering, 2005)
This paper presents a new approach for determination of vibration response of the triply articulated Space Shuttle Remote Manipulator System (SRMS) with large rigid overhanging payloads. In contrast to other researchers dynamic modelling is based on the exact eigenvalue analysis of the two main flexible links with a rigid end effector and payload, including the effect of interaction of the Shuttle. A wide range of SRMS configurations and payloads with joints free and locked is examined for bang-bang slews and with all joints locked for payload positioning using Shuttle thruster firing.
Paper given at Dynamics and Control of Systems and Structures in Space (DCSSS), 5th conference, Kings College, Cambridge, July 2002